PENINGKATAN KUALITAS PRODUK MELALUI MANAJEMEN PRODUKSI DAN INOVASI KEMASAN PADA USAHA KOPI BUBUK PUSAKO BUNDO - Malse anggia; Meiki Eru Putra; Sari Octavera (UIN Sunan Kalijaga, 2022)
This Community Service Program (PkM) aims to solve the difficulties faced by the Pusako Bundo coffee business in Kenagarian Pasie Laweh. The problems faced by partners are the production system that is still simple, the low production capacity so that producers have not met market needs. Efforts to improve product quality are carried out with assistance and training in production management. The activities carried out are in the form of increasing knowledge in the processing of coffee processing processes with the application of technology, so as to be able to prepare raw material needs and make production records, know product sanitation and innovation efforts. The implementation of the community service program has been able to provide good packaging, and provide knowledge to partners about good production systems to produce products with better quality and activity have a significant impact on the sustainability of the partner's business and have a significant impact on the sustainability of partners' businesses.